A modification of the method of fundamental solutions for solving 2D problems with concave and complicated domains. (1st February 2021) - Dezfouli, N. Koochak; Hematiyan, M.R.; Mohammadi, M.
Abstract: To solve various problems in complicated and concave domains by the method of fundamental solutions (MFS), it is required to consider a large number of source and collocation points that increases the computational time of the analysis. This paper suggests a modification to the MFS, which can make it more efficient and reliable for solving applied problems in complicated domains. In the proposed method, each pseudo source is converted to two or more number of sub-sources with equal intensities. Therefore, the total number of sources is increased while the number of unknowns is not increased. By this approach we will be able to reduce the distance between the main and the pseudo boundaries and therefore modeling the problems with complicated boundaries can be performed effectively. The proposed method is investigated for a scalar field problem, i.e. the Laplace equation, and a vector field problem, i.e. elastostatic problem. It is shown that by using the proposed method, in addition to reducing the calculation time, the condition number of the coefficient matrix also significantly decreases. By solving several numerical example problems, it is observed that the presented method can obtain accurate solutions by using a small number of collocation points.